Updated search for the flavor-changing neutral-current decay D0→μ⊃+μ⊃- in pp̄ collisions at √s=1.96 TeV - Aaltonen, T; Álvarez González, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Appel, J; Apresyan, A; Arisawa, T; Artikov, A; et al. (2010)
We report on a search for the flavor-changing neutral-current decay D0→μ⊃+μ⊃- in pp̄ collisions at √s=1.96TeV using 360pb⊃-1 of integrated luminosity collected by the CDF II detector at the Fermilab Tevatron collider. A displaced vertex trigger selects long-lived D0 candidates in the μ⊃+μ⊃-, π⊃+π⊃-, and K⊃-π⊃+ decay modes. We use the Cabibbo-favored D0→K⊃- π⊃+ channel to optimize the selection criteria in an unbiased manner, and the kinematically similar D0→π⊃+π⊃- channel for normalization. We set an upper limit on the branching fraction B(D0→μ⊃+μ⊃-)<2.1×10⊃-7(3.0×10⊃-7) at the 90% (95%) confidence level. © 2010 The American Physical Society.